PENGARUH KOMPOSISI CANGKANG KEMIRI - BARIUM KARBONAT PADA BAJA KARBON RENDAH MENGGUNAKAN METODE PACK CARBURIZING - Febrian Titok; Agung Supriyanto; Edi Sarwono; Nugroho Tri Atmoko (Teknika, 2025)
The pack carburizing process is a heat treatment method applied to metals by heating the material until it reaches the austenite phase to enhance its physical and mechanical properties. This study aims to examine the effect of varying carbon mixture compositions on the hardness and microstructure of steel. The heating process was carried out using a furnace at 930°C for 4 hours. Characterization was conducted through Scanning Electron Microscopy – Energy Dispersive X-ray (SEM–EDX), Vickers hardness testing according to ASTM E92 standards, and wear testing using the Oghosi method. The results show that the pack carburizing treatment successfully increased the material’s hardness up to 129.72 HV, approximately 30.8% higher than the untreated specimen. The specific wear test directly correlated with hardness, where specimens with higher hardness demonstrated superior wear resistance. A carbon composition of 70% produced the lowest wear rate, measured at 0.58380 mm³/kg·m. Therefore, the pack carburizing process improved mild steel’s hardness and wear resistance, with a 70% carbon composition providing the most optimal results.